A Randomized Phase IIb Study of Mavrilimumab and Golimumab in Rheumatoid Arthritis. Issue 1 (27th December 2017) - Weinblatt, Michael E.; McInnes, Iain B.; Kremer, Joel M.; Miranda, Pedro; Vencovsky, Jiri; Guo, Xiang; White, Wendy I.; Ryan, Patricia C.; Godwood, Alex; Albulescu, Marius; Close, David; Burmester, Gerd R.
Abstract : Objective: This 24‐week, phase IIb, double‐blind study was undertaken to evaluate the efficacy and safety of mavrilimumab (a monoclonal antibody to granulocyte–macrophage colony‐stimulating factor receptor α) and golimumab (a monoclonal antibody to tumor necrosis factor [anti‐TNF]) in patients with rheumatoid arthritis (RA) who have had an inadequate response to disease‐modifying antirheumatic drugs (DMARDs) (referred to as DMARD‐IR) and/or inadequate response to other anti‐TNF agents (referred to as anti‐TNF–IR). Methods: Patients with active RA and a history of DMARD‐IR (≥1 failed regimen) or DMARD‐IR (≥1 failed regimen) and anti‐TNF–IR (1–2 failed regimens) were randomized 1:1 to receive either mavrilimumab 100 mg subcutaneously every other week or golimumab 50 mg subcutaneously every 4 weeks alternating with placebo every 4 weeks, administered concomitantly with methotrexate. The primary end points were the American College of Rheumatology 20% improvement (ACR20), 50% improvement, and 70% improvement response rates at week 24, percentage of patients achieving a Disease Activity Score in 28 joints using C‐reactive protein level (DAS28‐CRP) of <2.6 at week 24, percentage of patients with a score improvement of >0.22 on the Health Assessment Questionnaire (HAQ) disability index (DI) at week 24, and safety/tolerability measures. This study was not powered to formally compare the 2 treatments. Results: At week 24, differences in the ACR20, ACR50, and ACR70 response rates between the mavrilimumab treatment group (n = 70) and golimumab treatment group (n = 68) were as follows: in all patients, −3.5% (90% confidence interval [90% CI] −16.8, 9.8), −8.6% (90% CI −22.0, 4.8), and −9.8% (90% CI −21.1, 1.4), respectively; in the anti‐TNF–IR group, 11.1% (90% CI −7.8, 29.9), −8.7% (90% CI −28.1, 10.7), and −0.7% (90% CI −18.0, 16.7), respectively. Differences in the percentage of patients achieving a DAS28‐CRP of <2.6 at week 24 between the mavrilimumab and golimumab groups were −11.6% (90% CI −23.2, 0.0) in all patients, and −4.0% (90% CI −20.9, 12.9) in the anti‐TNF–IR group. The percentage of patients achieving a >0.22 improvement in the HAQ DI score at week 24 was similar between the treatment groups. Treatment‐emergent adverse events were reported in 51.4% of mavrilimumab‐treated patients and 42.6% of golimumab‐treated patients. No deaths were reported, and no specific safety signals were identified. Conclusion: The findings of this study demonstrate the clinical efficacy of both treatments, mavrilimumab at a dosage of 100 mg every other week and golimumab at a dosage of 50 mg every 4 weeks, in patients with RA. Both regimens were well‐tolerated in patients who had shown an inadequate response to DMARDs and/or other anti‐TNF agents.